El estanco de aguardiente en Costa Rica: formación de Estado y política fiscal (1821-1837) - D'Alolio Sánchez, Ileana (2014)
This essay studies the fiscal policy that led to the monopoly of sugar cane alcohol in Costa Rica and the significance of its income to the treasury, as fiscal policy achievements were not only tax growth but also the expansion of sugar cane production and liquor industry. It argues that fiscal policy over aguardiente monopoly had an enormous impact, both economically and politically, on state formation. This study shows as well another side of “localism” and the complex political context of the first half of the nineteenth century.